EcoLingua: Optimizing Indonesian Learning through Lumen5 in Digital Era - Izhar; Yuniarti, Fatma; Nurjannah, Aan (The Study Program of English Education of Palangka Raya University, 2025)
This scholarly investigation examines the evolution and application of Lumen5-based video instructional media for Indonesian language pedagogy with a specific emphasis on environmental themes. Employing a Research and Development (R&D) methodology through the ADDIE framework, the inquiry produced five interactive videos that address various environmental challenges, including forest fires, flooding, waste management, landslides, and the maintenance of school hygiene. The research encompassed extensive evaluations involving 10th-grade students, utilizing a combination of qualitative and quantitative methodologies to evaluate the efficacy of the video-centric learning paradigm. Findings indicated a 30% enhancement in students' understanding of environmental concepts in comparison to conventional text-based instructional strategies. Moreover, 80% of the students indicated heightened engagement with the educational content, while 75% exhibited advancements in their digital literacy competencies. The utilization of Lumen5's AI-driven platform was found to be effective in producing interactive, visually stimulating materials that are appealing to Generation Z learners. By aligning with the Merdeka Curriculum and integrating local environmental contexts, this inquiry presents a scalable framework for augmenting both language instruction and environmental awareness in the context of the digital era. The outcomes imply that AI-enhanced video learning platforms possess the potential to effectively reconcile the divide between traditional educational approaches and modern instructional requirements while fostering environmental consciousness among learners.